# (9y-2)(2.1-7y)=0

## Simple and best practice solution for (9y-2)(2.1-7y)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so dont hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

## Solution for (9y-2)(2.1-7y)=0 equation:

(9y-2)(2.1-7y)=0
We add all the numbers together, and all the variables
(9y-2)(-7y+2.1)=0
We multiply parentheses ..
(-63y^2+18.9y+14y-4.2)=0
We get rid of parentheses
-63y^2+18.9y+14y-4.2=0
We add all the numbers together, and all the variables
-63y^2+32.9y-4.2=0
a = -63; b = 32.9; c = -4.2;Δ = b2-4acΔ = 32.92-4·(-63)·(-4.2)Δ = 24.01The delta value is higher than zero, so the equation has two solutionsWe use following formulas to calculate our solutions:$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(32.9)-\sqrt{24.01}}{2*-63}=\frac{-32.9-\sqrt{24.01}}{-126}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(32.9)+\sqrt{24.01}}{2*-63}=\frac{-32.9+\sqrt{24.01}}{-126}$

`